A. Bernard Knapp, Late Bronze Age Cyprus: A Reassessment of Settlement Structure and Society. SIMAL Pocket- Book 192. - Kiely, Thomas (Journal of Greek Archaeology, 2025)
The work under review here is effectively an extended essay on the Cypriot Late Bronze Age attractively packaged as a small monograph (so complete with hardcovers, excellent illustrations and an index) and dedicated to two titans of modern Cypriot archaeology, Vassos Karageorghis and Eddie Peltenburg. The explanation in the Preface that the book was published in this format because it was in this series that the author produced their first single-authored book in 1986 seems rather slight, and from what follows it will be clear – to this reviewer at least – that the overall project should have been allowed to mature for longer and certainly make use of a bigger barrel. The preface also nods at how the focus has shifted away from the Late Bronze Age as the most studied period of Cypriot prehistory.